Knowledge Networks, Solidarity, and Entrepreneurship: Towards a Theoretical-Empirical Framework - Rosa Azalea Canales García; Noelly Karla Sarracino Jiménez (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales)
A knowledge network is defined as a form of social interaction designed to complement and enhance the benefits derived from the exchange of knowledge. In this regard, entrepreneurship can illustrate how these network structures influence the success or failure of a nascent business. The aim of this study is to analyze how knowledge networks, grounded in trust and solidarity, impact entrepreneurial activity by fostering synergies that promote innovation and employment. To this end, the theoretical-conceptual model called Knowledge Networks Based on Solidarity in Entrepreneurship is proposed. The research adopts a qualitative methodology based on the case study method, focusing on Company M, located in Toluca, State of Mexico, which specializes in the commercialization of construction tools and moldings. The selection of this profit-oriented company allows for the examination of whether entrepreneurial actions are solely motivated by profit maximization or, on the contrary, encompass the formation of knowledge networks characterized by trust and solidarity. A limitation lies in the very nature of the case study, which leads to context-specific findings that are not generalizable. However, the results validate the proposed theoretical-empirical framework, as the analysis reveals a positive correlation between solidarity and knowledge networks within the entrepreneurial domain.